2021
DOI: 10.1101/2021.12.15.472822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein Posttranslational Signatures Identified in COVID-19 Patient Plasma

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a highly contagious virus of the coronavirus family that causes coronavirus disease-19 (COVID-19) in humans and a number of animal species. COVID-19 has rapidly propagated in the world in the past 2 years, causing a global pandemic. Here, we performed proteomic analysis of plasma samples from COVID-19 patients compared to healthy control donors in an exploratory study to gain insights into protein-level changes in the patients caused by SARS-CoV-2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…A number of studies have previously undertaken a discovery proteomics approach to study the perturbation of the plasma proteome during acute infection, 23 including serial proteomics in mild or low symptom individuals, 24 and in hospitalized patients. 25 , 26 In line with previous works and using our assay that was enriched for neuroinflammatory biomarkers, we found that drivers of proteomic perturbation include oxidative stress markers 27 (e.g., QSOX1), metabolic reprogramming factors 28 (e.g., FGF21) and cell adhesion molecules 29 (e.g., NCAM2). However, plasma proteome signatures of severe hospitalized patients are expectedly different from ours as a result of acute inflammatory changes that would occur not just from initial infection but from the subsequent cascade of events that are not COVID-specific, such as mechanical ventilation or prolonged immobilisation.…”
Section: Discussionsupporting
confidence: 88%
“…A number of studies have previously undertaken a discovery proteomics approach to study the perturbation of the plasma proteome during acute infection, 23 including serial proteomics in mild or low symptom individuals, 24 and in hospitalized patients. 25 , 26 In line with previous works and using our assay that was enriched for neuroinflammatory biomarkers, we found that drivers of proteomic perturbation include oxidative stress markers 27 (e.g., QSOX1), metabolic reprogramming factors 28 (e.g., FGF21) and cell adhesion molecules 29 (e.g., NCAM2). However, plasma proteome signatures of severe hospitalized patients are expectedly different from ours as a result of acute inflammatory changes that would occur not just from initial infection but from the subsequent cascade of events that are not COVID-specific, such as mechanical ventilation or prolonged immobilisation.…”
Section: Discussionsupporting
confidence: 88%
“…[4][5][6][7] The uncertainty in disease severity and progression makes uniform COVID-19 management difficult, indicating that patients could benefit from a precision medicine approach. 8-12 Among the next generation technologies used to investigate COVID-19, 10,[13][14][15][16][17][18][19][20][21][22][23][24][25]…”
mentioning
confidence: 99%
“…We consider PTMs as most probable way of generating of fig. 1 In a recent study, proteomes of Covid-19 patients and healthy donors were compared [7]. Global analysis of PTMs demonstrated a marked up-and down-regulation in such PTMs as phosphorylation, glycosylation, citrullination, and arginylation in Covid-19 patients compared to healthy donors.…”
Section: Resultsmentioning
confidence: 99%